2022
DOI: 10.1101/2022.07.12.22277528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causal associations of education, lifestyle behaviors, and cardiometabolic traits with epigenetic age acceleration: a Mendelian randomization study

Abstract: Background: GrimAge acceleration (GrimAgeAccel) and PhenoAge acceleration (PhenoAgeAccel) are DNA methylation-based markers of accelerated biological aging, standing out in predicting mortality and age-related cardiometabolic morbidities. Whether and to what extent modifiable risk factors are likely to influence GrimAgeAccel and PhenoAgeAccel, if causally established, could shed light on contributors to aging process and intervention targets for preventing age-related diseases and improving healthy longevity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“… 38 Even when accounting for body mass index and body fat percentage, waist circumference remained associated with insulin sensitivity in a population of adults aged 50 to 95 years. 38 In a study of 34 710 European adults, higher waist circumference was identified as a causal risk factor for accelerated epigenetic age, 39 adding to the existing literature on waist circumference and epigenetic age. 40 To our knowledge, there are no existing longitudinal studies examining waist circumference as a mediator between childhood stress and accelerated biological age.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Even when accounting for body mass index and body fat percentage, waist circumference remained associated with insulin sensitivity in a population of adults aged 50 to 95 years. 38 In a study of 34 710 European adults, higher waist circumference was identified as a causal risk factor for accelerated epigenetic age, 39 adding to the existing literature on waist circumference and epigenetic age. 40 To our knowledge, there are no existing longitudinal studies examining waist circumference as a mediator between childhood stress and accelerated biological age.…”
Section: Introductionmentioning
confidence: 99%